Pathophysiological analysis of the renal function by cystatin C in the formation of renal stones 0.6-1.0 cm in size in conditions of treatment with apparatus lithotriptor DUET MAGNA - Y. E. Rohovyy; O. I. Ariychuk (Kazimierz Wielki University, 2017)
In the article pathophysiological analysis of changes of the renal function by Cystatin C with the development of nephrolithiasis with the presence of stones 0.6-1.0 cmin size upper, middle kidney pelvis and the upper third of the ureter with using shock-wave lithotripsy, litotriptor DUET MAGNA (Dyrex) was made.